Using Buck's Fascia as an Integral Covering in Urethroplasty to Restore the Anatomical Structure of the Penis in One-Stage Hypospadias Repair: A Multicenter Chinese Study Comprising 1,386 Surgeries - Yin Zhang; Min Chao; Wei-ping Zhang; Yun-man Tang; Hai-chen Chen; Kai-ping Zhang; Ru-gang Lu; Xian-sheng Zhang; Dong-hua Lou (Frontiers Media S.A., 2021)
Objectives: The objective of the study is to investigate the feasibility and efficacy of urethroplasty with a Buck's fascia integral-covering technique (BFIC) to wrap and restore the normal anatomical structure of the penis in one-stage hypospadias surgery.Methods: One-stage surgeries for hypospadias management were performed using BFIC from January 2016 to September 2020 at four high-volume medical centers in China. The technique integrates Buck's fascia with glans wings to mobilize and wrap the urethra and restore penile anatomical relationships. The clinical data, postoperative follow-up data, and complications were recorded, and the results were analyzed.Results: A total of 1,386 patients were included in the study: 1,260 cases of primary hypospadias and 126 cases of re-operations; distal in 382 cases (27.6%), mid-shaft in 639 (46.1%), proximal in 365 (26.3%); tubularized incised plate (TIP) in 748 cases, inlay-graft in 124, onlay-graft in 49, Mathieu in 28, free-tube graft urethroplasty in 406, and 31 of hybrid procedures. One thousand one hundred forty-two patients (82.4%) were found to have penile curvature (>10°) after artificial erection and all corrected by dorsal plication/s or transection of the urethra plate (UP) simultaneously. The median followed-up time was 27 months (6-62). A total of 143 (10.3%) complications were recorded: 114 (9.0%) in the primary operations and 29 (23%) in the re-operations, 15 (3.9%) in distal hypospadias, 61 (9.5%) in mid-shaft, and 67 (18.4%) in proximal. The complication rate in UP preservation and transection was 10.1 and 10.8%, respectively. Of all case complications, there were 73 (5.2%) of fistula, 10 (0.6%) of dehiscence, 22 (1.6%) of meatal stenosis, 21 (1.5%) of stricture, 6 (0.7%) of diverticulum, and resident curvature in 11 cases (1.2%). The overall complication rate in TIP and free-tube procedure was 9.8 and 9.9%, respectively, and fistula occurred in primary TIP of 33 cases (4.9%).Conclusions: Buck's fascia with the glans can be used as an integral covering technique in one-stage distal to proximal hypospadias and primary or re-operative hypospadias repair. It is safe, feasible, and effective for the repair of hypospadias.